The Real Practices of Modern Trends of Management Accounting and Their Impact on Competitive Ability: A Survey Study on Selected Industrial Companies Listed in the Saudi Stock Exchange Market - Malo-Alain, Alaa; Alazzam, Farouq (Jordan Journal of Business Administration, 2016)
The present research aimed mainly to identify and analyze the real practices of modern trends of management accounting in the industrial companies listed in the Saudi stock exchange market and their impact on enhancing competitiveness. The research society consisted of all industrial companies listed in the Saudi stock exchange market during the year 2016 amounting to around 61 companies. The research sample consisted of 12 industrial companies which had been chosen based on certain criteria. 120 questionnaire forms have been distributed to 12 industrial companies; i.e., 10 questionnaire forms for each company, targeting accountants and financial managers. The total number of the collected questionnaires was 118, where 8 questionnaires were neglected due to lack of information and hence 110 questionnaires were analyzed which represented around 91.5% of the total distributed questionnaires. The study adopted various statistical measures to analyze the data using (SPSS) software, such as: arithmetic means, frequencies, one sample t-test, as well as ANOVA. The study came up with the following main findings: there is an interest in applying the practices and methods of modern management accounting in industrial companies listed in the Saudi stock exchange market. The study further found that modern management accounting methods contribute to strengthen the competitiveness of industrial companies listed in the Saudi stock exchange market. Furthermore, the study revealed a statistically significant relationship between applying the modern managerial accounting methods and enhancing the competitiveness of industrial companies listed in the Saudi stock exchange market. The study also found no statistically significant differences at the level of significance (0.05) or less between the responses of the study sample regarding the degree of applying the modern management accounting methods in industrial companies listed in the Saudi stock exchange market due to the variables (practical experience and training). Finally, the study found that there are certain difficulties in the application of modern management accounting methods in industrial companies listed in the Saudi stock exchange market.